(untitled) (Eurasian Research Bulletin, 2023)
This article talks about the improvement of reading, comprehension, communicative skills and oral speech on specialty in a foreign language with the help of various educational materials and different teaching methods. It also discusses aneffective way to test listening comprehension, which is closely related to the development of pronunciation skills.